DAM DEVELOPMENT AND FOOD SECURITY OF DIRECTLY AFFECTED HOUSEHOLDS: A CASE STUDY IN JATIGEDE DAM, SUMEDANG, WEST JAVA - Suwartapradja, Opan Suhendi; Iskandar, Budiawati Supangkat; Mulyanto, Dede; Iskandar, Johan (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The Jatigede Dam construction project has caused many residents in the inundation area of the Jatigede reservoir to move to new areas. The affected households by the Jatigede Dam in new places must adapt to obtain sources of income for food and other necessities. This research aims to elucidate the agroecosystem production, off-farm jobs, and food adequacy and food security of the affected people of Jatigede Dam in Jatimekar Hamlet, Jemah Village. The research method used was a combination of qualitative and quantitative. The results revealed that the affected households of the Jatigede Dam Development Project who live in Jatimekar Hamlet, Jemaah Village, have less agricultural land ownership such as rice fields, mixed gardens and home gardens than before the Jatigede Dam existed. Consequently, some of the affected households of Jatigede Dam, they are also involved in various off-farm jobs. Based on food security, it shows that the affected people of Jatigede Dam in Jatimekar Hamlet, Jemah Village are in a vulnerable condition, due to low family income, and farming also faces various problems, such as water scarcity in the dry season and agricultural inputs, such as inorganic fertilizers, pesticides, and plant seeds have high price.